Editorial - Chou, Ralph (Canadian Journal of Optometry, 2025)
For the past several years, one of the long-term projects of the editorial team has been to have the Canadian Journal of Optometry (CJO) included in at least one of the major indexing services like PubMed. This would not only raise the profile of the CJO but also make it more attractive to optometric scholars who need to publish in peer-reviewed publications. In the last year or so, it became clear that our publisher was unable to support changes required by the indexing services to which we had applied. As a result, a call for proposals was launched last winter to find a new publisher. The final selection was made in late June. As it happened, we learned that our previous publisher abruptly ceased all operations in early July. Fortunately, the summer issue with a nominal publication date of June 1, 2025, was already in the mail and the online (official) version published before this happened. This issue marks the first with our new publisher, Keith Communications Inc. KCI was quick to offer to begin work immediately on this issue. The masthead on the table of contents page reflects the change. The result will be an improved CJO that we hope will be acceptable not only to indexing services but also to you, our readers. There is another change in the masthead to note. Dr. Benoit Tousignant has been the Academic Editor since 2018. He is taking on more duties at l’École d’optométrie in Montreal and left his position with CJO in June. I thank him for his contributions to the CJO and wish him all the best.